Come home already! [book with audioplayer] - John, Jory ([Library Ideas, LLC], 2018)
An excited Duck wants to hang out with Bear. But Bear's gone fishing for a whole week and is happy to finally get a second alone. What will Duck do while Bear is gone? How will he survive without his best pal?!